2017
DOI: 10.1088/1361-6560/aa5bc7
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo study of I-125 prostate brachytherapy with gold nanoparticles: dose enhancement with simultaneous rectal dose sparing via radiation shielding

Abstract: We investigate via Monte Carlo simulations a new 125I brachytherapy treatment technique for High-Risk prostate cancer patients via injection of Au nanoparticle (AuNP) directly into the prostate. The purpose of using the nanoparticles is to increase the therapeutic index via two synergistic effects: enhanced energy deposition within the prostate and simultaneous shielding of organs at risk from radiation escaping from the prostate. Both uniform and non-uniform concentrations of AuNP are studied. The latter are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…The first assumption, which is the basis of the correction for lack of CPE, neglects the so-called sink effect of the GNP [35], i.e. that electrons traversing the GNP will lose more energy than when traversing the same volume of water.…”
Section: Uncertainty Of the Cpe And Spe Correctionsmentioning
confidence: 99%
“…The first assumption, which is the basis of the correction for lack of CPE, neglects the so-called sink effect of the GNP [35], i.e. that electrons traversing the GNP will lose more energy than when traversing the same volume of water.…”
Section: Uncertainty Of the Cpe And Spe Correctionsmentioning
confidence: 99%
“…This attenuation effect at the macroscopic scale was explained in recent theoretical study from Brivio et al, which revealed a decrease of the dose to the rectum and to the urethra as a consequence to a combination of 125 I brachytherapy and Au NPs. 15 A detailed description of the "attenuation effect" undergone by the 103 Pd photons interacting with Au atoms inside of the injection volume, is available in the Supporting Information. Also, the isodose line profiles decrease more abruptly for the 103 Pd:AuNPSeed compared to the TheraSeed.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, smaller volumes of energy deposition should not be seen as limitative: instead, the smaller volumes associated with the 103 Pd:AuNPSeed model, coupled to the sharper isodose fall-out simulation profiles, is an indication of enhanced treatment precision. Applied to the scale of the organs, this could help in avoiding excess dose deposition to the urethra and to the rectum, as suggested by the recent theoretical study of Brivio et al 15 The attenuation effect caused by the Au atoms present in the injection volume allows the dose to be deposited very locally. The photons emitted within the "cloud" of NPs interact with Au, a high-Z element, and transfer their energy much closer to the injection site compared with the insertion of conventional seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Brivio et al studied the effect of uniform and nonuniform distributions of GNPs in a prostate theoretical Monte Carlo model . Dose enhancement increased as a function of local GNPs concentration ( Figure ).…”
Section: Adaptation Of Brachytherapy Dosimetry To Include the Radiosementioning
confidence: 99%